Kuliah Kerja Nyata: Pengabdian Kepada Masyarakat Melalui Kegiatan Digitalisasi UMKM di Desa Kemiri - Diajeng Oxana Khoirunnisa Wardhani; Moch Harris Ramadhan; Reza Risanti; Budi Prabowo (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Goal 8 of the Sustainable Development Goals (SDGs) focuses on the importance of achieving inclusive and sustainable economic growth, with the aim of creating decent jobs and equalising economic welfare, especially in rural areas. The Community Service Program carried out by the Thematic State Defense Student Community Service (KKN) Group 5 Wave 2 UPN Veteran East Java is a program to empower the potential of the community around Kemiri Village by socialising the digitalisation of MSMEs so that they can achieve economic growth. The main objective of the MSME digitalisation activity is to improve the ability of MSME players to use digital technology effectively. The method of implementing community service activities in Kemiri Village includes the initial observation stage, interview stage, programme planning stage, programme implementation stage, and evaluation stage. The MSME digitalisation activities that have been carried out by KKN-T Bela Negara Group 5 Wave 2 UPN Veteran East Java students in Kemiri Village have been successful by cooperating with 14 MSMEs of which 11 MSMEs are willing to be assisted with registration on Google Maps, 2 MSMEs are willing to make banners, and 1 MSME is willing to be assisted with QRIS registration.